Examining the Causes of Obesity and Their Effects on the Physical and Psychological Well-Being of Women Leaders in Qatari Society: An Empirical Study - Alghuwayri , Azizah Nouh; El-Gohary , Hatem (Journal of Ecohumanism, 2024)
This study aims to identify the main factors contributing to the rise in obesity rates among women in Qatari society and to examine its impact on their physical and psychological health. The research follows a positivist approach, using a questionnaire distributed to a random sample of distinguished women in leadership positions. Two hundred twenty-four questionnaires were distributed, and 220 were fully completed, forming the actual sample size. The study employs fundamental statistical analyses, including demographic distributions and percentage frequencies, and statistical tools, such as correlation analysis and regression analysis, to understand relationships between variables like poor dietary habits, physical activity levels, genetic predisposition, and socio-cultural norms. The findings indicate that poor dietary habits, cultural and social factors, genetic predisposition, and lack of physical activity are the main contributors to the high obesity rates among Qatari women. Obesity leads to physical health issues such as high blood pressure, diabetes, and heart disease, as well as psychological effects like increased depression and lower self-esteem. This study provides reliable data and statistics for future research, aiding a deeper understanding of obesity in Qatar. It offers practical recommendations for improving the health of women leaders through health education programs and the promotion of physical activity. Additionally, the study contributes to public awareness about obesity risks and encourages an improved quality of life within Qatari society.